Methods of tactical driving of cargo complex - Окороков, Андрій Михайлович (Eastern-European Journal of Enterprise Technologies, 2012)
While solving the problem of improving the quality of transport services of cargo owners through the creation of transport cargo complexes in traffic centers it is necessary to apply a systematic approach. In connection with this, the model of the transport cargo complexes should have a hierarchical structure. Each hierarchical level is characterized by its problems and methods of testing. Meanwhile, the obtained dependences of the lower levels serve as input data for studies at higher levels. At least two of these levels must be considered: tactical (operational) and strategic (long-term). At each of these levels a control systems of appropriate organizational units or individual objects, enabling optimization of both these units and transport cargo complexes as a whole, must be designed. The purpose of the article is to explain the process of designing of transport cargo complexes control techniques at the tactical level, i.e. in operational work. The basis of such control is the distribution of cargo operation between stations that are in transport cargo complexes, considering not only their technical equipment, but also stochastic factors that affect the performance and workload. The technique designed allows not only the implementation of this distribution, but also develops a task on cargo operations fulfillment at stations in accordance with the developed plan of the optimal distribution